A Scanning Electron Microscopic Study of Platelets of Certain Animal Species - Jain, N. C (Thrombosis and Haemostasis, 1975)
Comparative morphology of platelets of the dog, cat, cow, horse, sheep, and goat was studied with the scanning electron microscope and was found generally similar. Most of the platelets were slightly biconvex or flat with relatively smooth surface and even contour. Some of these platelets had few short marginal filaments, or small shallow depressions or tiny protuberances on the surface. A small number of platelets exhibited surface irregularity and few long pseudopods which were thought to result from platelet activation during the processing of blood. The number of such irregular platelets increased in stored blood and in blood fixed at 4° C.